The Efforts Of Sharia Micro Financial Institutions In Increasing Community Income (Case Study Of Bank Wakaf Mikro Honai Sejahtera Papua) - Shimah Fauziah Yeubun; Muhammad Anang Firdaus; Fachrudin Fiqri Affandy (Universitas Islam Negeri (UIN) Walisongo Semarang, 2021)
AbstractPurpose - This study aims to determine and analyze the effort of the Honai Prosperous Micro Waqf Bank in Papua in increasing community income in Heram District, Jayapura, Papua Province. Micro Waqf Bank is one of the government programs for low-scale communities.Method - This research uses a qualitative method with a case study approach. Primary data are collected from several informants who have related duties and functions such as managers, boarding school leaders, and customers from the Honai Sejahtera Micro Waqf Bank. While secondary data includes data from documents, literature, and academic studies and research. The data that has been collected is then processed and analyzed using a field analysis approach from Miles and Huberman.Result - The results of this study indicate that Honai Sejahtera Micro Waqf Bank improve the communities' income in Heram District by providing a loan for business capital using the Qardh. Besides that, the community felt the positive impact of their existence.Implication - Local Governments need to work together with LKMS to empower communities to escape poverty.Originality- This research focuses on increasing people's income through Islamic Microfinance Institution (LKMS) in Papua Province which has never been studied previously.